(untitled) (Annals of Medical Research, 2023)
Aim: Psoriasis is a disease characterized by chronic inflammation of the skin and small joints that causes serious deterioration in quality of life. Inflammation, angiogenesis and fibrosis plays a significant role in the disease pathogenesis. Fibroblast growth factor 2 (FGF2) is a vigorous mitogenic agent and a molecule associated with pathways that are effective in the pathogenesis of psoriasis. The purpose of this study is to determine the level of patients with FGF2 in the serum of psoriasis and to determine the change in the level of this molecule according to the severity of the disease. Materials and Methods: 96 patients with psoriasis and 100 healthful were included in this study. The level of FGF2 was measured by ELISA method from serum samples obtained from blood samples taken from those included in the study. The results were compared with the healthful control group. Patients with psoriasis were grouped as mild, moderate, severe and very severe. FGF2 levels were compared in patients grouped according to disease severity. Results: Serum FGF2 levels were found to be higher in psoriasis patients compared to the healthful control group (p<0.0001). When psoriasis patients were checked against the healthy control group according to the severity of the disease, serum FGF2 levels were found to increase in the moderate, severe and very severe patient groups (p<0.001). Conclusion: Elevated serum FGF2 level in psoriasis patients was revealed for the first time. As the severity of the disease increases, the increase in the serum FGF2 level shows that this molecule may be effective in the pathogenesis of psoriasis and may be the target molecule in treatment.